Christian Martyrdom in Late Antiquity (300-450 AD): History and Discourse, Tradition and Religious Identity - Gemeinhardt, Peter (Arbeiten zur Kirchengeschichte, 2012)
The present volume's focus lies on the formation of a multifaceted discourse on Christian martyrdom in Late Antiquity. While martyrdom accounts remain a central means of defining Christian identity, new literary genres emerge, e.g., the Lives of Saints (Athanasius on Antony), sermons (the Cappadocians), hymns (Prudentius). Authors like Eusebius of Caesarea and Augustine employ martyrological language and motifs in their writings, while beyond the borders of the Roman Empire, new martyrs' narratives can be found. The volume thus enlarges and specifies our knowledge of this important Christian discourse. Peter Gemeinhardt, Georg-August-University of Göttingen, Germany; Johan Leemans, Catholic University Leuven, Belgium.